Bacterial Cell Surface Deformation under External Loading - Yun Chen (American Society for Microbiology, 2012)
ABSTRACT Viscoelastic deformation of the contact volume between adhering bacteria and substratum surfaces plays a role in their adhesion and detachment. Currently, there are no deformation models that account for the heterogeneous structure and composition of bacteria, consisting of a relatively soft outer layer and a more rigid, hard core enveloped by a cross-linked peptidoglycan layer. The aim of this paper is to present a new, simple model to derive the reduced Young’s modulus of the contact volume between adhering bacteria and substratum surfaces based on the relationship between deformation and applied external loading force, measured using atomic force microscopy. The model assumes that contact is established through a cylinder with constant volume and does not require assumptions on the properties and dimensions of the contact cylinder. The reduced Young’s moduli obtained (8 to 47 kPa) and dimensions of the contact cylinders could be interpreted on the basis of the cell surface features and cell wall characteristics, i.e., surfaces that are more rigid (because of either less fibrillation, less extracellular polymeric substance production, or a higher degree of cross-linking of the peptidoglycan layer) had shorter contact cylinders and higher reduced Young’s moduli. Application of an existing Hertz model to our experimental data yielded reduced Young’s moduli that were up to 100 times higher for all strains investigated, likely because the Hertz model pertains to a major extent to the more rigid peptidoglycan layer and not only to the soft outer bacterial cell surface, involved in the bond between a bacterium and a substratum surface. IMPORTANCE The viscoelastic properties of the bond between an adhering bacterium and a substratum surface play a role in determining bacterial detachment. For instance, removal of an oral biofilm proceeds according to a viscoelastic failure model, and biofilm left behind after toothbrushing has been found to possess expanded bond lengths between adhering bacteria due to viscoelastic deformation. Current elastic deformation models are unable to distinguish between the soft outer bacterial cell surface and the hard core of a bacterium, enveloped by a peptidoglycan layer. Therefore, here we present a simple model to calculate the Young’s modulus and deformation of the contact volume between an adhering bacterium and a substratum surface that accounts for the heterogeneous structure of a bacterium.